Implementación de normatividad aplicable en Colombia en un sistema de iluminación de emergencia y alarmas sonoras contra incendio en el Bloque C de la Universidad Antonio Nariño Sede Valledupar. (2020)
Fire emergencies are eventualities that can happen anywhere and at any time, are incidents that, although we are not exempt from them happening, if we can prevent, alert and counter them. The regulations in Colombia that refer to fire detections are quite broad and clearly determine the reactions that people must have depending on the degree of intensity or severity of the same. The protection of people will depend on the reaction they take when facing an emergency, so we decided to contribute to the university our learning in this field, so that members of the academic community can have a prevention tool that they can use. in the place with the highest number of people.